On The Job Training Report Airport Electrical Engineering Study Program Diploma Program Three Class XX At Sultan Mahmud Badaruddin II Airport Palembang - Nainggolan, Delon Hesekiel; Usman, Usman; Akbar, Muhammad Caesar (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
On The Job Training (OJT) which is carried out at the airport is a work training program designed to provide practical experience to cadets in applying the theories they have learned during their education at the Medan Aviation Polytechnic. Sultan Mahmud Badaruddin II Airport Palembang has various electrical load needs that vary in each of its buildings, including terminals and several office units. The main source of electricity for this airport comes from PLN, solar panels (solar cells), and diesel generators as emergency power sources. After carrying out On The Job Training (OJT) activities at Sultan Mahmud Badaruddin II Airport Palembang, I draw the following conclusions about the implementation of OJT: Keep equipment in optimal condition with maintenance and repairs carried out daily, weekly, monthly, and annually in the electrical unit according to the predetermined schedule. During the implementation of On The Job Training, cadets can find out about activities and problems that occur at Sultan Mahmud Badaruddin II Airport Palembang. Gaining experience, learning, kinship and responsibility during OJT activities leaves a good impression on cadets Cadets can apply the theory they get during their education and then compare it with conditions in the field. In doing work or repairs, they do not do it alone because technicians are a team that helps each other.